2021
DOI: 10.1155/2021/4704771
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Valine Ameliorated Gut Health and Accelerated the Development of Nonalcoholic Fatty Liver Disease of Laying Hens

Abstract: Valine is an important essential amino acid of laying hens. Dietary supplemented with BCAAs ameliorated gut microbiota, whereas elevated blood levels of BCAAs are positively associated with obesity, insulin resistance, and diabetes in both humans and rodents. General controlled nonrepressed (GCN2) kinase plays a crucial role in regulating intestinal inflammation and hepatic fatty acid homeostasis during amino acids deficiency, while GCN2 deficient results in enhanced intestinal inflammation and developed hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 68 publications
7
32
0
Order By: Relevance
“…The metabolism of various cells in the body produces a large number of reactive oxygen species and other substances. Laying hens are susceptible to producing excessive reactive oxygen species leading to intestinal oxidative stress due to the genetic selection for long-laying eggs [ 20 ]. Sufficient studies have proved that butyrate performed powerful antioxidant functions whether in vivo or in vitro [ 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of various cells in the body produces a large number of reactive oxygen species and other substances. Laying hens are susceptible to producing excessive reactive oxygen species leading to intestinal oxidative stress due to the genetic selection for long-laying eggs [ 20 ]. Sufficient studies have proved that butyrate performed powerful antioxidant functions whether in vivo or in vitro [ 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a substrate for the synthesis of TG, fatty acids can be esterified with glycerol sterol backbones, generating TGs or sterol esters (SEs), respectively, and then stored in LDs ( 36 ). Our recent report indicated dietary valine treatment dramatically increased the concentration of TG in the serum and liver with increasing dietary levels ( 33 ). We first investigated the effects of dietary valine on liver fatty acid synthesis, and we found that dietary valine supplementation dramatically improved the contents of liver ACLY, NEFA, HDL, and VLDL ( P < 0.05) ( Figures 2C,D,E,G ), whereas the content of liver FASN showed an increase first and then decreased with the increase of dietary valine levels ( P < 0.05) ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Our recent reports demonstrated that diet-supplemented valine has significantly altered the serum-free amino acid profile of laying hens. Additionally, long-term exposure to high levels of dietary valine at 0.74 and 0.79% has accelerated the development of NAFLD of laying hens by promoting lipogenesis and inhibiting fatty acid oxidation mediated by GCN2-eIF2α-activating transcription factor 4 (ATF4) ( 32 , 33 ). NAFLD induced by excessive dietary valine resulted in strengthening oxidative stress, ER stress, and inflammatory response ( 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and C. perfringens require leucine and isoleucine for their growth whereas Escherichia coli do not depend on these AA and thus the variability in the supply of such AA could favor certain groups of bacteria in their competitiveness against others in the GIT of poultry. Jian et al. (2021b) studied the effect of supplemental valine fed to 33-wk-old laying hens where basal control diet contained 0.59% total valine and the supplemented diet had 0.79% valine.…”
Section: Effects Of Bcaa On Intestinal Development Immunity and Micro...mentioning
confidence: 99%